Exercise is recreation not medicine - Andy Smith (Elsevier, 2016)
Purpose: This paper responds to the question, is exercise medicine? It does so using a qualitative case study that proposes that exercise is recreation. The study (1) describes and reflects upon an exercise is recreation metaphor, (2) establishes the principles and processes used to develop a sport park within which exercise is recreation, and (3) presents a comparative analysis of the exercise is recreation approach with a UK quality framework for "exercise referrals". Methods: Four years of documentation were collated and placed into 14 categories: (1) university strategies, (2) plans of the site, (3) policy documents, (4) minutes of a steering group, (5) contemporary documents, (6) organisational charts, (7) responses to local government policies on sport, (8) consultation documents, (9) operational procedures, (10) facility specifications, (11) partnership agreements, (12) material relating to the university's work on events, (13) notes on the universities sport department, and (14) timetables. These data were analysed through a 4-stage process which used recreation as the analytical theme for a comparative analysis. Results: The characteristics of the exercise is recreation metaphor in this case are (1) a focus on the experience of the user, (2) the promotion of well-being, (3) the importance of community, (4) embracing inclusivity, (5) sport, (6) aesthetics, and (7) leisure time. The principles and processes used to develop the sport park were (1) custodianship, (2) partnerships, (3) values, (4) inter-professional working, (5) local heritage, (6) change, (7) the natural park environment, and (8) "riding the bike as you build it". The comparative analysis with a UK quality framework for "exercise referrals" clearly shows a difference from an exercise is recreation approach. Conclusion: Exercise is recreation and may enable individuals and communities to reach a state of well-being.